Pembelajaran Jarak Jauh Pendidikan Kewarganegaraan: Tantangan Dalam Penerapan Merdeka Belajar Di Era Disrupsi - Riza Alrakhman (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
The purpose of this research is to find out the disruption of the digital era in distance learning civics education in the application of independent learning. The research method used is grounded theory. Sources of data in this research are documents related to the disruption of the digital era in distance learning, citizenship education in the application of independent learning, data validation by conducting triangulation. The results of the study show that distance learning civics education in the application of independent learning in the digital era disruption requires attention, namely: 1) The application of independent learning in the digital disruption era results in a focus on material that is important or essential, so that learning is more in-depth and not rushed -hurry up. 2) In independent distance learning learning in the era of digital disruption makes students more active, independent and able to motivate themselves. The conclusion of this article is that in distance learning civic education brings and the application of independent learning can be a source of learning for students by accessing information that will help them improve the learning process